VALIDITAS LEMBAR KERJA PESERTA DIDIK ELEKTRONIK PEMBELAJARAN BIOLOGI SMA KONSEP SISTEM RESPIRASI MANUSIA - Huridah, Muliya; Noorhidayati, Noorhidayati; Putra, Aminuddin Prahatama (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
21st century education requires students and educators to master information, media, and technology to have 6C competencies. One of the teaching materials that is by the demands of 21st-century education is the electronic Student Worksheet. This study aims to describe the validity of the results of the development of electronic worksheets on the concept of the Human Respiratory System for Class XI Senior High School. This research and development use an analysis model (Analysis), design (Design), development (Development), implementation (Implementation), and evaluation (Evaluation) (ADDIE) (Rayanto & Sugianti, 2020), which is limited to the formative evaluation stage. Data collection techniques using validity instruments The research subjects were 3 experts, namely 1 media expert, 1 material expert, and 1 biology subject partner educator at Senior High School (SMAN 4 Banjarmasin). The results of testing the validity of the development of electronic worksheets on the concept of the Human Respiratory System for SMA Class XI show that they are very valid, with an average score of 4.39, which means that electronic worksheets are very valid to be used as teaching materials, especially on the concept of the human respiratory system.